CIVILIZATIONAL THRESHOLDS AND THE TRANSFORMATION OF SCIENTIFIC KNOWLEDGE - Shamsutdynova-Lebediuk, Tetyana; Lebedyuk, Yelizaveta; Shamsutdynov, Bakhodir (Sworld-Us Conference proceedings, 2025)
This paper examines the epistemological and ethical implications of technogenic civilization’s accelerated development, focusing on three interrelated global crises: the threat of self-annihilation through weapons of mass destruction, the ecological desta